The Era Of Misinformation: United States, Russia And European Union - Martins, Marco (2018)
The US elections mean the opening of a new era in the search for global rebalancing, in the triangular relationship between the United States, Russia, and China. The election of Donald Trump sparked a wave of unprecedented protests in America's electoral history. It exposes an anti‐system image that purports to erase policy options implemented by its predecessors, as well as externally reassess the role of NATO. Misinform is a concept that was introduced by Vladimir Putin on a scale of a possible hybrid war with the United States and the European Union. It is therefore important to understand how the European Union will position itself in international relations, by adapting its foreign, defense and security policies, in addition to the consequences of Brexit, needing to rediscover its way in the name of European construction with the emergence of new actors from the BRICS to cyberspace.